Vrednotenje regionalnega razvoja Spodnjega Posavja z vidika sonaravnosti - Vintar Mally, Katja (Geografski vestnik, 2002)
An evaluation of regional development of Spodnje Posavje region in the second half of the 1990s was made in the light of sustainable development concept. Several social, economic and environmental aspects of regional development were selected and studied to this end. Resultant from the study are the priority tasks which are to be considered in the future regional development: to reinvigorate regional economy, cut down unemployment rate, stimulate the development in rural areas, rise the educational level of the population, protect water and improve its quality, and treat waste properly. These tasks will also have to be taken into account in the future regional policy and regional developmental programs.
Keywords: environmental protection; varstvo okolja; ecology; ekologija; sonaravni razvoj; regionalni razvoj; Lower Sava Valley; Posavje